The HPV101 E7 protein shares host cellular targets and biological activities with high-risk HPV16 E7 - Maya K. Gelbard; Miranda Grace; Annika von Schoeler-Ames; Ida Gnanou; Karl Munger (Tumour Virus Research, 2025)
Human papillomaviruses (HPVs) are a diverse family of viruses with over 450 members that have been identified and fully sequenced. They are classified into five phylogenetic genera: alpha, beta, gamma, mu, and nu. The high-risk alpha HPVs, such as HPV16, have been studied the most extensively due to their medical significance as cancer-causing agents. However, while nearly 70% of all HPVs are members of the gamma genus, they are almost entirely unstudied. This is because gamma HPVs have been considered medically irrelevant commensals as most of them infect the skin and are not known to cause significant clinical lesions in immunocompetent individuals. Members of the gamma 6 HPVs, however, have been detected in the anogenital tract mucosa and HPV101 has been isolated from a premalignant cervical lesion. Moreover, gamma 6 HPVs have a unique genome structure. They lack E6 proteins but in place of E6, they encode unique, small hydrophobic proteins without any close viral or cellular homologs that have been termed E10. Here, we report that HPV101 E7 shares biochemical activities with the high-risk alpha HPV16 E7, including the ability to target the pRB and PTPN14 tumor suppressors for degradation. This study underscores the importance of further characterizing HPV101 and other unstudied HPV species.